The Essence of Financial Management - Buckley Adrian; Myddelton R. D (Prentice Hall, 1995)
This book is concise, analytical and uniform in its approach to the key topics of good business practice. Preface, Introduction, Business Finance, The Financial Environment, Accounting, Problems in Finance, Interest Rates, Time, Inflation, Risk and Required Return, Cash, Uses of Cash, Cash and Profit, Cash Planning, Working Capital, Working Capital as a Whole, Stocks, Debtors, Spontaneous Creditors, Basic Capital Project Appraisal, Background, Simple Appraisal Methods, Measuring Profit Over Time, Discounted Cash Flow Methods, Capital Project Appraisal Refinements, Taxation, Capital Disinvestment, Inflation, Risk and Uncertainty, Capital Budgeting, Borrowing, General Features, Reducing the Lender's Risk, The Cost of Debt, Other Types of Debt, Valuing Debt, Ordinary Shares, Shareholders' Funds, The Stock Exchange, Issuing Equity Shares, Dividend Policy, Valuing Equity, Modern Portfolio Theory, Other Share Valuation Methods, Corporate Finance, Cost of Capital, Gearing, Capital Structure, The Corporate Life Cycle, Mergers and Reconstructions, Reasons for Mergers, Merger Statistics, Index.